Foreign media preference for negative frames in coverage of terrorism in sub-saharan Africa (2017)
Foreign media have been criticised for promoting Afro-pessimism and preference for negative frames in their representation of Africa. This is more pronounced especially in reporting of terrorism in the Sub-Saharan Africa. But are the African media less guilty of this preference for negativity? This paper aimed to answer this question by assessing how news media reported terrorism in the Sahel. To achieve this objective, some existing empirical studies that investigated media coverage of terrorism in the Sub-Saharan Africa were reviewed. The review shows that the news media—both foreign and African media—in their presentation of terrorism in the Sahel, still preserved the dominant paradigm of media preference for negativity in news reporting. Foreign news media, with limited knowledge of the real situation in Africa, used negative frames to report the Sub-Saharan Africa as a region of crises. Ironically, the performance of African media in respect of their coverage of terrorism in the Sahel is ambivalent and less impressive; as the African media tried to perform their warning surveillance function by alerting the state to the potential danger posed by terror groups, they also used frames that exaggerate the impact and dominance of the insurgents. This preference for negativity by news media in the coverage of terror could set negative public agenda, further escalate the spate of terror, and threaten public peace in the Sub-Saharan Africa.